Границы жанра в автобиографии В. В. Набокова «Память, говори» (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
The article studies the peculiarities, of autobiography as a literary genre, its stages and its features in V. Nabokov’s work «Memory, speak». It deals with the main topics of the novel, the author’s way of creating «special reality» as the genre’s mark and self-irony as one of the most important principles to express author’s selfconscience.